STUDY OF BALAGHAH: The Context of Understanding Al-Qashar in Surah Al-Kafirun Verse 6 in Relation to Various Attitudes of Religious Tolerance in Indonesian Society. - Mitra, Rohma; Rahma, Nazwa Awallul (Jurnal Al-Hibru, 2025)
Indonesia is a country with religious diversity, so the issue of religious tolerance is very important to maintain social harmony. One of the verses of the Qur'an that is often used as a basis for understanding tolerance is Surah Al-Kafirun verse 6, "Lakum diinukum waliyadin." This verse contains the concept of al-qashar from the perspective of balaga studies, namely the concept of affirming differences in beliefs without coercion and hostility. This study aims to examine the public's understanding of the meaning of Al-qashar in the verse and its relationship to the attitude of religious tolerance in Indonesia. The methodology used is descriptive qualitative, with data collection techniques in the form of literature studies and semi-structured interviews with religious leaders and the Muslim community. The survey found that most respondents understood the verse as an expression of recognition of religious differences, not a justification for inter-religious conflict. The meaning of Al-Qasr is actually understood as an ideological prohibition that encourages peaceful coexistence. Therefore, a contextual understanding of Surah Al-Kafirun verse 6 plays a role in strengthening the attitude of religious tolerance, especially in the pluralistic Indonesian society. This study recommends strengthening thematic interpretive literacy in religious education to expand moderate and comprehensive understanding.